THE MEDIATION EFFECT OF ELECTRONIC WORD OF MOUTH-BASED IMAGE AND SERVICE QUALITY ON VISIT INTENTION - Adjie Muhajir; Adya Hemawati; Septo Pawelas Asro (Universitas Sarjanawiyata Tamansiswa, 2026)
This study examines the effects of electronic word of mouth (e-WOM) and service quality on patients’ visit intention, with hospital image serving as a mediating variable at Soelastri Dental and Oral Hospital in Surakarta. A quantitative cross-sectional design was employed involving 100 general patients selected through purposive sampling. Data were collected using a structured questionnaire with a five-point Likert scale and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that e-WOM has a positive and significant effect on hospital image (β=0.225; T=7.523; p<0.05), as does service quality (β=0.336; T=4.268; p<0.05). Direct effects indicate that e-WOM (β=0.194; T=2.089; p<0.05), service quality (β=0.474; T=4.936; p<0.05), and hospital image (β=0.225; T=2.048; p<0.05) significantly influence visit intention. Mediation analysis confirms that hospital image significantly mediates the relationship between e-WOM and visit intention (β=0.121; T=1.854; p<0.05) as well as between service quality and visit intention (β=0.076; T=1.881; p<0.05). These findings extend healthcare marketing literature by highlighting institutional image as a critical psychological mechanism linking digital information and service experience to patient behavioral intentions. Practically, the results underscore the importance of integrating digital reputation management with consistent service quality improvement to strengthen competitive positioning in self-pay healthcare institutions.